POPULATION STRUCTURE OF DIPTEROCARPACEAE SPECIES IN KETAMBE RESEARCH STATION, GUNUNG LEUSER NATIONAL PARK, ACEH TENGGARA - Rizki Amelia; Saida Rasnovi; Essy Harnelly (Jurnal Natural, 2019)
Ketambe Research Station is one of the oldest and most complete stations in the world which has abundant biodiversity. The Dipterocarpaceae is one of the family identified as growing in the forest area of Ketambe Research Station. Ecologically, Dipterocarpaceae has several limiting factors for its growth and distribution and the most determining factors are soil factors and climate. Dipterocarpaceae is also known as nest and source of food for orangutans, namely Shorea spp. Therefore, it is necessary to conduct research that aims to determine the population structure of Dipterocarpaceae species in Ketambe Research Station. The method used Quadrat Sampling Technique. Theplacement of the sampling plot was randomly carried out in 25 plots with an area of 1 ha. The result showed that there were three species of Dipterocarapaceae found in this station i.e., Parashorea lucida, Shorea johorensis and Hopea dryobalanoides. Based on the population structure pyramid, P. lucida will survive and develop in the future S. johorensis and H. dryobalanoides, on the other hand, are estimated to decrease or hardly survived in the future.